2011
DOI: 10.5194/os-7-27-2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cross-shelf water transport on nutrients and phytoplankton in the East China Sea: a model study

Abstract: Abstract.A three dimensional coupled biophysical model was used to examine the supply of oceanic nutrients to the shelf of the East China Sea (ECS) and its role in primary production over the shelf. The model consisted of two parts: the hydrodynamic module was based on a nested model with a horizontal resolution of 1/18 degree, whereas the biological module was a lower trophic level ecosystem model including two types of phytoplankton, three elements of nutrients, and biogenic organic material. The model resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 30 publications
4
49
1
Order By: Relevance
“…Hence our observed imbalance might be partially due to nitrification. In addition, atmospheric deposition and advective fluxes induced by river plume, frontal eddies, and tides on the shelf of the ECS could also contribute to the high nitrate assimilation (Chen et al, 2003a(Chen et al, , 2003bNakamura et al, 2005;Kodama et al, 2011;Zhao and Guo, 2011).…”
Section: New Nitrogen Sources In the Ecs And The Adjacent Areamentioning
confidence: 98%
“…Hence our observed imbalance might be partially due to nitrification. In addition, atmospheric deposition and advective fluxes induced by river plume, frontal eddies, and tides on the shelf of the ECS could also contribute to the high nitrate assimilation (Chen et al, 2003a(Chen et al, , 2003bNakamura et al, 2005;Kodama et al, 2011;Zhao and Guo, 2011).…”
Section: New Nitrogen Sources In the Ecs And The Adjacent Areamentioning
confidence: 98%
“…9f). This cross-shore fluctuation has a significant ecological impact because of the connected nutrient transport (Zhao and Guo, 2011). Ren et al (2015) observed a cross-shore flux in the inshore area, which was triggered by the transition of northeasterly to southwesterly winds.…”
Section: Water Exchange In the Inshore Area Induced By Windmentioning
confidence: 99%
“…This can be either through wind-driven eastern boundary systems, where nutrient-rich water is upwelled from depths around 200-300 m, or through kinematic upwelling along the inner edge of western boundary currents, such as occurs across the Agulhas Bank south of Africa (Carter and D'Aubrey, 1988). The influence of cross-shelf water transport from the Kuroshio on nutrients and phytoplankton in the East China Sea is looked at by Zhao and Guo (2011).…”
Section: Chemical Oceanographymentioning
confidence: 99%
“…More recently, Roughan et al (2006) examined how across-shelf structure in velocity and hydrography affect the retention (inshore) and export (offshore) of nutrients, plankton and larvae, in the context of the spatial structure of the coastal currents during wind-driven upwelling and relaxation on the northern Californian Shelf. Similarly, Zhao and Guo (2011) look at the influence of cross-shelf water transport on nutrients and phytoplankton in the East China Sea.…”
Section: Physical Control On Biologymentioning
confidence: 99%